Reproducible computational biology experiments with SED-ML: the Simulation Experiment Description Markup Language - Waltemath, Dagmar; Adams, Richard; Hucka, Michael; Sahle, Sven; Snoep, Jacky L.; Le Novère, Nicolas (BMC systems biology, 2011)
The increasing use of computational simulation experiments to inform modern biological research creates new challenges to annotate, archive, share and reproduce such experiments. The recently published Minimum Information About a Simulation Experiment (MIASE) proposes a minimal set of information that should be provided to allow the reproduction of simulation experiments among users and software tools.